Exposure to proton pump inhibitors is associated with the development of pediatric autoimmune diseases - Räisänen, Laura; Viljakainen, Heli; Kolho, Kaija-Leena (Frontiers in Pediatrics, 2023)
Proton pump inhibitors (PPIs) have been associated with decreased gut microbiota diversity. Disrupted gut microbiota composition has been reported in several autoimmune diseases (ADs), such as type 1 diabetes mellitus (DM), autoimmune thyroiditis (AIT), juvenile idiopathic arthritis (JIA), and inflammatory bowel diseases (IBD). We investigated whether PPIs are associated with the development of ADs in children and concluded that PPI exposures could be related to the onset of ADs, especially IBD.